Grammatical Cohesion in Jo March’s Utterances in Little Women: A Textual Analysis - Al-Fath, Tastrid Nur; Zulianti, Hajjah; Febriyanti, Febriyanti (Journal of Language Intelligence and Culture, 2025)
This study aims to analyze the use of grammatical cohesion in Jo March’s dialogues of the Little Women movie, focusing on how frequent the types can occur as well as its function to convey meaning. This study addresses the gap by focusing how cohesive devices are used to shape Jo March’s way of speaking and the way she expresses her character. The data were collected from Jo’s utterances from the script, while the content analysis by Ary et al., was employed to analyze the data. The writer checks the data validity using peer debriefing and theory triangulation using Paltridge’s and Halliday’s theory. Several types the writer found from the script are reference, conjunction, substitution, and ellipsis. The results indicate that conjunctions were the most frequent types from the script, with 46%. Followed by reference with 26%, ellipsis 17%, and substitution 11%. These numbers show that Jo tends to speak quickly and connect her ideas closely together. The references help her link one idea to another, while ellipsis and substitution reveal her natural, informal way of talking. In other words, the function of each grammatical cohesion types is to create unity and clarity in a text by linking its elements, avoiding unnecessary repetition, and making the flow of contents easier to follow.